West-East: Roles and Impacts from a Linguist’s Perspective - Srichampa, Sophana (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
This article presents aspects of West and East relations from the colonial period to the present day. Language comes with power. Since colonial times, colonial languages, most notably English, accompanied the British as the main colonial power and industrial leader for about two centuries. Even in the following centuries, English was still important because of the power of the US economy as well as the influence of technology in the world today. Similarly, the popularity of Chinese has followed the economic progress and politics of China in the world. West and East have learned each other across the region and beyond region through Areal studies and Regional studies. Moreover, language and culture are important keys to forging friendships as soft power is linked to good relationships with other countries. The world's great powers, including France, Britain, India, Germany, America, Japan, Korea, China and Russia have set up cultural organizations and export their “brands” all over the world as good cultural diplomacy. Globalization has both positive and negative impacts on the way we live with technological advances that must be communicated through English. As a result, many countries who have developed human resources to support their development in the digital age by means of long-standing bi-lingual / multicultural policies through education, will be able to advance and adapt to all rapid changes. But countries such as Thailand that do not cultivate human resource potential systematically through good educational planning, will be adversely affected. Leaders of such countries need to be aware of this and prepare in a determined and measured way so as not to lag behind in the region.